Pengembangan Model Pembelajaran Problem-Map Untuk Mengembangkan Sikap Pelestarian Lingkungan Hidup Mahasiswa IKIP Budi Utomo Malang - Erfitra Rezqi Prasmala; Dyah Ayu Widya Ningrum; Dwi Candra Setiawan (IKIP Budi Utomo Malang, 2016)
In the midst of technological development and increasing need to encourage people to large exploitation of environment, resulting in demage and environmental pollution. Humans is natural destroyer agent, in an efforto preserve the environment need to developed conceptual continuously. Based on observations, shows that students still have the attitude of environmental conservation is low. Design of learning not to lead to the settlement solving in the enviroment arounda the student, so that a low sense love for the environment and fostering poor attitude of environmental conservation. he learning model is applied to improve the condition is Problem-Map. This learning model implemented in several stages: (1) Problem Based Learning and (2) Making the Mind Map in solving problems. This research will develop learning model Problem-Map, the development of research methods using models Borg and Gall (1983). Based on trial results through the activities of PTK learning model suggests that the model of teaching Problem-Map can developing attitude of environmental conservation students at IKIP Budi Utomo Malang